Concentration of Phthalate Esters in Bottled Water: A Case Study in Effurun, Delta State, Nigeria (Journal of Environmental Science Studies, 2023)
Phthalate esters (PAEs), a group of chemical compounds, are extensively used as additives in plastics. The objective of this study was to determine how much of a few target PAEs have leached into various samples of drinking water packaged in PET bottles in Effurun, Delta State, Nigeria as well as how ambient temperature, sunshine exposure, and cold storage conditions have affected the concentration of PAE. The concentrations of Di-ethyl-phthalate (DEP), di-butyl-phthalates (DBP), benzyl-butyl-phthalate (BBP), di-n-octyl phthalate (DnOP), and Bis-(2-ethyl-hexyl) phthalate (DEHP) were determined in bottled water samples. The concentrations of PAEs were determined using a gas chromatography coupled with a mass sepctroscopy analyzer (GC-MS). Phthalate compound was observed to be in all bottled water placed under different storage conditions; cold storage (CW), ambient storage (AW), and sunlight storage (SLW) for a period of 2, 4, 8, 12 and 16 weeks. However, the greatest leaching effect was observed in PET bottled water placed sunlight conditions for sixteen weeks with concentrations of; DEHP (2.1-11.2) µg/L, DEP (0.98-3.87) µg/L, DBP (2.98-13.8) µg/L. The results from this study indicated that, under various storage conditions, DEP, DBP and DEHP from PET bottles may leach more into the drinking water over a period of time under different storage conditions. The result additionally gave indication that DEHP; a known endocrine disruptor, with anti-androgenic and possible human carcinogen effects, exceeded the 6 µg/L USEPA Maximum Contamination Level (MCL) in drinking water, and also greater than 8 µg/L which is the indicated MCL by the World Health Organization (WHO).